Assistance in Production Cost Management for Weavers - Muh. Ramli; Arianto Dangkeng; Hardianti Pertiwi; Hasrul Wijaya (www.amertainstitute.com, 2025)
This community engagement program aims to enhance the financial management capabilities of weaving artisans in Kampung Tenun Rongkong, Luwu Utara, by strengthening their understanding and application of production cost management. Traditional weavers generally rely on intuitive methods when determining production expenses and pricing, which results in inaccurate cost estimates, inconsistent pricing strategies, and limited financial sustainability. To address this gap, a participatory and problem-based approach was implemented through several stages, including preliminary assessment, training workshops, hands-on mentoring, and evaluation. The program introduced key concepts related to cost classification, cost of goods manufactured (COGM), cost of goods sold (COGS), budgeting techniques, and simple financial record-keeping tailored to small-scale weaving enterprises. The results indicate significant improvements in artisans’ knowledge of production cost components, accuracy in cost calculation, and their ability to record daily expenditures using structured worksheets. Participants also demonstrated increased awareness of overhead costs and adopted more rational pricing strategies based on actual cost data. Mentoring activities further facilitated behavioral changes, particularly in tracking expenses and exploring more efficient raw material procurement options. Despite these positive outcomes, challenges related to varying literacy levels and limited digital readiness remain. The program highlights the importance of continuous assistance and the integration of broader capacity-building topics, such as digital marketing and market access, to ensure long-term sustainability for traditional weaving communities.